2011
DOI: 10.1063/1.3658392
|View full text |Cite
|
Sign up to set email alerts
|

Localized surface plasmon-enhanced electroluminescence from ZnO-based heterojunction light-emitting diodes

Abstract: We demonstrate the surface plasmon (SP) enhanced n-ZnO/AlN/p-GaN light-emitting diodes (LEDs) by inserting the Ag nanoparticles (NPs) between the ZnO and AlN layers. The ultraviolet/violet near band edge emission of the device is significantly enhanced while the green defect-related emission is modestly suppressed compared to the LEDs without Ag NPs. The red-shift of electroluminescence (EL) peak and the reduced photoluminescence decay lifetime of ZnO suggest that the improved EL performance of the device with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…In the contrast, the excitation of LSPs is more facile and it can be easily achieved in many metal nanoparticles (e.g., Au, Ag, Al and etc.) [13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…In the contrast, the excitation of LSPs is more facile and it can be easily achieved in many metal nanoparticles (e.g., Au, Ag, Al and etc.) [13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…Among these materials, ZnO/metal hybrids have been intensively investigated. It has been demonstrated that the NBE emission of ZnO can be enhanced by incorporating various kinds of noble metals, such as Ag [13], Au [14,15], and Pt [16]. Meanwhile, the DL emission band of ZnO is usually suppressed, resulting in an improved monochromaticity of UV-light emission.…”
Section: Introductionmentioning
confidence: 98%
“…Various hybrid structures, such as ZnO/oxides [9], ZnO/polymer [10], ZnO/carbon nanotubes [11], ZnO/graphene [12], and ZnO/metal [13], have been investigated in this regard. Among these materials, ZnO/metal hybrids have been intensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…When the energy of excitons/photons in a semiconductor is similar to the electron vibrational energy of metal SPs, the energy will be coupled into the SPs and finally scattered into free space as radiation [8]. The formation of such new recombination path improves the internal quantum efficiency of LEDs [9] as well as their light extraction efficiency. The coupling with metal NPs, which is a near-field interaction, induces a significant luminescence improvement in ZnO-based p-n junction LEDs via Ag nanoparticles decoration [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%